The Significance of Vitamin D in the Development of the Periodontium (International Journal of Food and Nutritional Sciences, 2022)
It has been known for a long time that one of the most important functions of this secosteroid is to regulate calcium levels, which allows vitamin D to play an important role in the preservation of skeletal health. There is a wealth of research that demonstrates a correlation between oral bone mineral density and some measure of systemic osteoporosis. This research also suggests that osteoporosis and low bone mass may be factors that contribute to the development of periodontal disease. In recent years, the nonskeletal effects of vitamin D have received increased attention for a number of different reasons. It has been established that a great number of cells that are not related with calcium homeostasis exhibit membrane receptors for vitamin D. [Citation needed] These include activated T lymphocytes and B lymphocytes, as well as cancer cells from the skin, placenta, pancreatic, prostate, and colon. In addition, vitamin D "insufficiency" is a worldwide epidemic, and epidemiologic data has connected this illness to a multitude of chronic health problems, including cardiovascular and autoimmune diseases, hypertension, and a number of malignancies. This condition is a worldwide epidemic. It is interesting to note that there is accumulating evidence supporting the concept of "continual vitamin D adequacy" in the context of the maintenance of periodontal health. This link between lower serum levels of vitamin D and higher gingival inflammation has been uncovered. It is possible that a significant part of this process is determined by the capacity of vitamin D to influence both the innate and the adaptive components of the host response. In this review, we will investigate the skeletal and nonskeletal activities of vitamin D, as well as its possible role in preventing damage to the periodontium and controlling the healing of periodontal wounds.